Study habits and academic performance in foreign language students - Orna Tiburcio, Luis Alberto (2022)
Objective. To determine the relationship between study habits and academic performance in students of English as a second language. Methods. Research with a quantitative approach, observational, descriptive, cross-sectional with a non-experimental and correlational design, for the collection of information on study habits, the inventory of study habits CASM-85 was used and for academic performance data, school records were used. The sample consisted of 208 students between 13 and 23 years old, who were selected through a simple random probabilistic sampling, from a population of 454. Results. There was a very low, positive and direct relationship between study habits and academic performance (Spearmans Rho=0.18; p=0,009), in the case of the relationship between the dimensions of study habits with academic performance, only the dimension dedication to homework was significant (Spearmans Rho=0,25; p-value=0,000), the others (study techniques, preparation for exams, attitude during classes and study environment) despite being positive none were significant (p-value>0.05) Conclusions. There is a statistically significant relationship, but not causal, between study habits in general and between its dimension dedication to homework and academic performance.